Kamus kejuruteraan kimia. - Dewan Bahasa dan Pustaka (Kuala Lumpur : Dewan Bahasa dan Pustaka, 1997)
Malay dictionary of chemical engineering terms and its meaning in English.
Includes bibliographical references (p. 500-501).
In Malay.
Keywords: Chemical engineering -- Dictionaries -- Malay; Malay language -- Dictionaries -- English; Chemical engineering -- Dictionaries; English language -- Dictionaries -- Malaysian; English language -- Dictionaries -- Malay